Upaya Guru Dan Kepala Madrasah Dalam Meningkatkan Prestasi Belajar Peserta Didik di MA Darul Istiqomah Srigading Kecamatan Labuhan Maringgai Kabupaten Lampung Timur Tahun 2024 - Ahmad Zamzuri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Education Management in this case has a strategic role in determining the direction of development of a nation. So, management of character education should be applied in every world of children's lives, starting from the family, school, even in their play environment. In this position character education requires strong cooperation with the education curriculum in schools, especially Madrasah-level Education where the education management implemented must be able to support the education of children's positive attitudes and behavior. Therefore, this study aims to describe and understand education management in madrasa education units and the implementation of education management in improving the education of students' interests, attitudes and behavior in South Sumatra (Madrasah Tsanawiyah Nurul Iman Margotani). This research method uses a qualitative approach with triangulation data collection techniques. The research location is at the Nurul Iman Margotani Education Foundation in the Madrasah Tsanawiyah Institute, Nurul Iman Margotani, Madang Suku II District, East Oku Regency. The results of the study show that the implementation of character education management in developing students' interests, attitudes and behavior is based on objective planning with clear and specific goals, has regular educational programs, develops activities in the form of intra-curricular, extracurricular, guidance and counseling program activities with goals as the formation of student character education, improving student skills in humanizing practices and other skills. Determination of character education management in developing students' interests, attitudes and positive behavior. in the form of long-term and short-term programs implemented by example, direction, assignment, habituation, and environmental creation. This affects the character of the santri in the form of leadership, discipline, trustworthiness, sincerity and decency. These conditions support the creation of an environment that is healthy and conducive to learning, everything that is heard, seen, and suggested by students is an element of education.